Unveiling digital democracy: social media’s catalyst role in enhancing political participation and public engagement - Puspasari, Erlina; Rahmanto, Andre Noevi; Sudarmo, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The increasing opportunities and levels of public participation are fundamental to democracy, and political participation is an integral part of the system. However, a comprehensive understanding of how social media impacts political participation is lacking. The objective of this study is to examine the role of social media in transforming public political participation by systematically observing the literature and analyzing the impact of digital transformation on citizens' political involvement through social media. This research uses a systematic literature review methodology to describe emerging trends in digital democracy studies and analyze them to increase comprehensiveness and comparability, in particular highlighting articles that cover various aspects of digital democracy, political participation, and the role of social media in the context of digital democracy. The analysis was carried out on fifteen articles published between 2018 and 2023. The research results found that social media plays a crucial role in building interactions and relationships between citizens, developing social networks, strengthening interpersonal relationships, and encouraging political involvement. Social media is used for various political activities, including advocacy, public consultation, monitoring, political campaigns, and sending direct messages to politicians and elected officials. The implications of this research suggest that social media is a powerful tool for increasing democratic engagement by enabling more accessible and widespread political participation.